2010
DOI: 10.1093/humrep/deq165
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the method of conception and embryo transfer procedure on mid-gestation placenta and fetal development in an IVF mouse model

Abstract: In vitro embryo culture affects fetal and placental development; this could explain the lower birthweight in IVF offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 40 publications
7
85
2
Order By: Relevance
“…However, the long-term effect of this IVF-induced female-specific epigenetic error should be further investigated. During the mid-gestation stage, E13.5 was selected for sampling based on developmental considerations, as the placental architecture and function is well established and spongiotrophoblast and labyrinthine areas can be clearly distinguished at this time (Delle Piane et al 2010). Although the implantation ability of IVF embryos was comparable with that of IVO embryos, we found that the abortion rate of IVF embryos is significantly higher than that of IVO embryos.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, the long-term effect of this IVF-induced female-specific epigenetic error should be further investigated. During the mid-gestation stage, E13.5 was selected for sampling based on developmental considerations, as the placental architecture and function is well established and spongiotrophoblast and labyrinthine areas can be clearly distinguished at this time (Delle Piane et al 2010). Although the implantation ability of IVF embryos was comparable with that of IVO embryos, we found that the abortion rate of IVF embryos is significantly higher than that of IVO embryos.…”
Section: Discussionmentioning
confidence: 91%
“…We used a well-established experimental design (Delle Piane et al 2010, Fauque et al 2010, Tan et al 2015 to test the sex-biased or sex-specific effects of the IVF process from pre-implantation to the prenatal stage (Fig. 1).…”
Section: Experimental Designmentioning
confidence: 99%
“…Low birth weight has also been linked to predisposition to cardiovascular diseases, diabetes, and stroke. A previous in vitro study of mouse embryos supported that in vitro embryo culture affects both fetal and placental weight during development [Delle Piane et al 2010]. In vitro culture of sheep or cattle embryos has been associated with abnormal skeletal and organ development [Walker et al 2000].…”
Section: Various Methods Are Needed To Monitor Genome Integrity Durinmentioning
confidence: 99%
“…Oocytes were obtained from superovulated C57Bl/ 6J female mice as described previously. 14,25 Briefly, female mice were injected with 5 IU of pregnant mare serum gonadotropin and 46 to 48 hours later with 5 IU of human chorionic gonadotropin (hCG). The following morning, oocytes were collected from the ampullae.…”
Section: Preimplantation Embryo Productionmentioning
confidence: 99%